PROTOCOL: Behavioral, information and monetary interventions to reduce energy consumption in households: A “living” systematic review - Tarun M. Khanna; Diana Danilenko; Mark Andor; Max Callaghan; Julian H. Elliott; Tim Repke; Luke A. Smith; Jorge Sanchez; T. V. Bhumika; Jan C. Minx (Campbell Systematic Reviews)
Abstract This is the protocol for a Campbell systematic review. The objectives are as follows: Our proposed systematic review and meta‐analysis will integrate the evidence available from all sources to answer the following questions: (1) to what extent can information, behavioral and monetary interventions reduce energy consumption of households in residential buildings? (average treatment effect of interventions) (2) what is the relative effectiveness of interventions? (account for heterogeneity in treatment effects across and within studies) (3) how effective are combinations of different interventions?